Proceedings of the 14th Workshop on Mobile Computing Systems and Applications 2013
DOI: 10.1145/2444776.2444799
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the potential of ride-sharing using call description records

Abstract: Ride-sharing on the daily home-work-home commute can help individuals save on gasoline and other car-related costs, while at the same time reducing traffic and pollution in the city. Work in this area has typically focused on technology, usability, security, and legal issues. However, the success of any ride-sharing technology relies on the implicit assumption that human mobility patterns and city layouts exhibit enough route overlap to allow for ride-sharing on the first place. In this paper we validate this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…For example, cell phone activities, commonly know as Call Description Records (CDR), are used for capturing human communication activities [3]. In addition, it is also used for recovering the human mobility trajectory [9], inferring demographics [6], and uncovering urban ecology [2].…”
Section: Related Workmentioning
confidence: 99%
“…For example, cell phone activities, commonly know as Call Description Records (CDR), are used for capturing human communication activities [3]. In addition, it is also used for recovering the human mobility trajectory [9], inferring demographics [6], and uncovering urban ecology [2].…”
Section: Related Workmentioning
confidence: 99%
“…In [18] authors analyse users' localizations collected by mobile phones to enable ride sharing among people with overlapped mobility routines on a daily base. The total number of circulating cars could be halved at the expense of 1 Km detours, if people that share the same home and work areas would also share their private cars.…”
Section: A Mobility Analysis For Ride Sharingmentioning
confidence: 99%
“…Therefore, potential of ridesharing is generally found to be lower in studies that account for this factor. For example, Cici et al (2013Cici et al ( , 2014 showed that a time window of 10-30 minutes results in 10-20% reduction in the number of cars in real-time situations if a delay time of 10 minutes and a detour distance of one kilometer are accepted by users. Without this time restriction, they show a higher ridesharing potential of up to 60%.…”
Section: Dynamic Versus Static Ridesharingmentioning
confidence: 99%